Pengaruh Service Experience dan Service Quality terhadap Loyalitas Pelanggan yang Dimoderasi oleh Kepuasan Pelanggan di Fitness Center Khusus Wanita di Kota Bandung - Septiarini, Eka (JSKK (Jurnal Sains Keolahragaan dan Kesehatan), 2023)
People now realize the importance of health as an investment for the future. This is marked by the development of a fitness center in Bandung. Women are quite selective in choosing a place to do their physical activity. Not all women are comfortable exercising in places mixed with the opposite sex. Service experience and service quality are two strategic variables that are important in increasing competitiveness. The objective  of this research is to observe the moderating effect of customer satisfaction of service experience and service quality on customer loyalty. This research was obtained by distributing questionnaires to 253 respondents (customers) who are actively doing sports at a women's fitness center. The process of quantitative analysis using simple regression method, multiple linear regression and MRA (Moderated Regression Analysis) analysis. The results show that the variable customer satisfaction moderates service experience and service quality on customer loyalty by 27.8% and 34.8%, respectively. Results of  this study showed customer satisfaction is moderating variabel on service experience and service quality to customer loyalty. Keywords: service experience, service quality, customer satisfaction, customer loyalty, fitness center